EKSPLORASI PASIR BESI KAWASAN PASIA PANEH NAGARI TIKU SELATAN KECAMATAN TANJUNG MUTIARA SEBAGAI BAHAN BAKU INDUSTRI DI SUMATERA BARAT - Yola Andani; Adree Octova (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. Iron sand is generally a beach of iron sand which is widely spread, including along the west coast of Sumatra, the southern coast of Java and Bali, the beaches of Sulawesi, East Nusa Tenggara, Maluku and the north coast of Papua. Iron sand contains magnetic minerals which are materials for building tools in modern life. The great potential in South Nagari Tiku must also be followed by a market that is able to absorb the product. To find out the market potential, it is necessary to analyze the quality of iron sand in both regions. So it can be determined whether the potential in the area can have economic value or not. Nagari Tiku Selatan is located in Tanjung Mutiara District, Agam Regency, West Sumatra Province. Area of Nagari Tiku Selatan: 31.42 KM2 or 15.27% of the total area of Tanjung Mutiara District. Nagari Tiku Selatan is the capital of the sub-district, located 20 KM from the district capital and 92 KM from the provincial capital. This study aims to determine the amount of resources (quantity) and quality of iron sand in the area, using a combination of direct exploration and indirect exploration. Based on the results of the study it was found that the resource of iron sand from the area obtained from handbor lithology was 199,680 tons while from geolistrik measurements the volume was 7,987,200 tons. The total area containing iron sand in the survey area is 249,600 m2 and the total survey area is 2.3 km2. With the specific gravity obtained from physical tests of 3.2. While the quality of iron sand in the area contains between 10-20% Fe2O3, while TiO2 content between 0.6-1.7% is obtained from the analysis of samples tested in the laboratory using the XRF method.Keywords: Iron Sand, Handbor, Geolistrik, Exploration, Resources